Analysis and Economic Evaluation of the Invasion of the Public Space with Improvements of Particulars, Case Study Urbanization Fuente Del Dorado (2023)
There is a diversity of urban regulations that refer to public space, its destination, use and enjoyment, but actually and outside the legislature, this ideal scenario is not fulfilled, either due to the omission of regulatory entities, regulation misund